Low molecular weight chitosan (∼20 kDa) exhibits in vivo anti-hyperglycemic effects through AKT/PI3K/FOXO pathway - Priyanka D․ N․; Harish Prashanth K․ V․ (Carbohydrate Polymer Technologies and Applications)
Diabetes, a metabolic syndrome, is a leading global cause of morbidity and mortality. Dietary polysaccharide intervention besides medication, helps in diabetes through managing blood glucose levels. The present study elucidates the anti-hyperglycemic mechanism of water-soluble LMWC (∼20 kDa), the chitosan derivative, in type-1 diabetic (T1DM) male Wistar rats induced by streptozotocin (STZ, 36 mg/kg b.w.). LMWC1 (100 mg/kg b.w.) and LMWC2 (250 mg/kg b.w.) were administered orally on alternative days for 4 weeks. LMWC lowered fasting blood glucose levels and improved symptoms like polyphagia, polydipsia, polyuria, and serum insulin levels in a dose-dependent manner. It also ameliorated hyperglycemia & dyslipidemia by mitigating the levels of pro-inflammatory factors and oxidative stress levels in the pancreas and liver. Additionally, LMWC increased the activity of key proteins involved in insulin signaling in these organs through the AKT/PI3K/FOXO pathway, enhancing insulin secretion and improving glucose metabolism in T1DM rats. This contributed to improved hepatic glycogen synthesis and suppression of gluconeogenesis in T1DM rats. In summary, LMWC could be an effective antidiabetic supplement, offering insights into dietary treatment for diabetes management.